TRIASSIC AND JURASSIC CALCAREOUS NANNOFOSSILS OF THE PIZZO MONDELLO SECTION: A SEM STUDY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
Pizzo Mondello is a ca. 500 m thick pelagic-hemipelagic succession cropping out in Sicily consisting of a nodular cherty limestone facies association of late Carnian to late Norian age. The uppermost portion was attributed to the Rhaetian and is represented by the plane-bedded Portella Gebbia Limestone. The section has been proposed as the stratotype for the base of the Norian stage. The calcareous nannofossil content of limestones was studied with Scanning Electron Microscope (SEM) in two portions of the Pizzo Mondello section, one within 'La Cava' that encompasses all the proposed horizons for the base of the Norian, and one within the Portella Gebbia Limestone in the uppermost part of the section.Calcareous nannofossil assemblages of the first portion display low diversity, being constituted exclusively by calcispheres, that may constitute up to 40% of the sediment volume. Species richness increases in the upper portion. Initially, samples are dominated by Prinsiosphaera triassica, a nannolith of unknown taxonomic affinity. Rare calcareous dinocysts (Thoracosphaera cf. geometrica) and coccoliths are present in few samples. Uppermost samples are still dominated by "calcispheres" comparable to Thoracosphaera, but also yield a variety of coccoliths and nannoliths.Calcareous nannofossil distribution was calibrated with conodont and radiolarian biostratigraphy. On the basis of this integrated work, specimens attributed to cf. Thoracosphaera, observed in the lower portion of the section, are late Carnian to early Norian, while samples dominated by Prinsiosphaera, with rare Thoracosphaera and coccoliths are Rhaetian. The calcareous nannofossil assemblage of the uppermost samples, along with radiolarians and the absence of conodonts, point to a Jurassic age (Pliensbachian) for the uppermost Portella Gebbia Limestone at Pizzo Mondello. In conclusion, the age of the uppermost part of the Pizzo Mondello section is Jurassic, i.e., younger than previously thought. Calcareous nannofossils are present from the base of section and exhibit a significant taxonomic diversity, thus providing an auxiliary biostratigraphic frame for the Rhaetian - Jurassic interval in this area.
Keywords: Upper Triassic; Lower Jurassic; Tethys; Calcareous nannofossils; Calcareous dinocysts; Conodonts; Radiolarians